Shared changes in angiogenic factors across gastrointestinal vascular conditions: A pilot study - Mc Namara, Deirdre; Douglas, Atiyekeogbebe R.; Holleran, Grainne; Smith, Sinead M. (My University, 2020)
BACKGROUND Neovascularisation is common to a variety of gastrointestinal (GI) disorders with differing aetiologies and presentations; usually affecting adults above 60 years. Shared angiogenic factors modulated by disease specific elements could be a common denominator and represent novel diagnostic and therapeutic targets. As yet, assessment of angiogenic factors across several GI vascular disorders associated with recurrent bleeding and anaemia has not been reported. AIM To assess serum levels of angiogenic factors in several intestinal vascular disorders. METHODS A case control study was performed in Tallaght University Hospital in patients with endoscopically proven small bowel angiodysplasia (SBA), portal hypertensive gastropathy (PHG), gastric antral vascular ectasia (GAVE) and non-bleeding, non-anaemic controls. Using enzyme-linked immunosorbent assay, concentrations of Angiopoietin 1 (Ang-1), Ang-2 and vascular endothelial growth factor (VEGF) were measured from 2 serum tubes of blood following informed consent. The relative expression of Ang-1 and Ang-2 and Ang-1/2 ratio was calculated and compared between groups. Statistical analysis was applied using a t-test, and a P value of < 0.05 was considered significant. RESULTS To date 44 samples were tested: 10 SBA, 11 PHG, 8 GAVE and 15 controls. Mean age 60 (range 20-85) years and 20 (45%) were males. Controls were significantly younger (49 years vs 66 years, P = 0.0005). There was no difference in VEGF levels between the groups (P = 0.6). SBA, PHG and GAVE Ang-1 levels were similar and were significantly lower than controls, (P = 0.0002, 95%CI: 241 to 701). Ang-2 levels were statistically higher in PHG and GAVE groups compared to controls (P = 0.01, 95%CI: 77.8 to 668) and as a result, also had a lower Ang-1/2 ratios compared to controls. While SBA Ang-2 levels were higher than controls, this did not reach statistical significance. Neither age nor haemoglobin level, which was similar between disease groups, could explain the difference. In addition, the median Ang-1/Ang-2 ratio for all patients was found to be significantly lower compared to controls, 8 vs 28 respectively, P = 0.001, 95%CI: -27.55 to -7.12. CONCLUSION Our novel pilot study suggests common alterations in Ang-1 and Ang-2 levels across several GI vascular disorders. Differences in Ang-1/Ang-2 ratios among vascular disorders compared to controls suggest disease-specific modulation.
PUBLISHED
Keywords: Gastric antral vascular ectasia; Portal hypertensive gastropathy; Angiodysplasia; Angiopoietins; Angiogenic factors; Recurrent bleeding; angiogenic factors; gastrointestinal bleeding; Health